2006
DOI: 10.1017/s0950268806007163
|View full text |Cite
|
Sign up to set email alerts
|

Trends in encephalitis-associated deaths in the United States

Abstract: The United States national mortality statistics and HIV/AIDS surveillance data were analysed to determine trends in encephalitis-associated deaths and to assess the impact of HIV infection on those deaths during 1979-1998, a period when ICD-9 codes were used for coding deaths in the United States. A total of 25125 encephalitis deaths were reported; 4779 of them (19%) had concurrent HIV infection. Overall encephalitis death rates remained stable, but they increased for groups where HIV infection was common and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 20 publications
1
25
0
1
Order By: Relevance
“…This study found that the downward trend noted during 1989-1998 in the US encephalitis-associated death rate continued through 1999-2008 [8]. The only annual rate increase identified during the study period was from 2001 to 2002, which corresponds to the introduction of WNV into the USA, and primarily affected the ≥65-year age group [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study found that the downward trend noted during 1989-1998 in the US encephalitis-associated death rate continued through 1999-2008 [8]. The only annual rate increase identified during the study period was from 2001 to 2002, which corresponds to the introduction of WNV into the USA, and primarily affected the ≥65-year age group [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Cause-of-death information is coded from a specific section on death certificates completed by the person certifying the death. The ICD-10 codes used to identify encephalitis-associated deaths were selected to be consistent with ICD-9 codes from previous encephalitis mortality studies (table 1) [7,8]. Encephalitis deaths were categorized into two groups: ‘specified encephalitis' using the specified encephalitis causes (ICD-10 codes) and ‘unspecified encephalitis' which included the remaining encephalitis death records (table 1) [15].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations